2018
DOI: 10.1172/jci99420
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap production contributes to pathogenesis in SIV-infected nonhuman primates

Abstract: Neutrophil extracellular traps (NETs) are involved in the pathogenesis of many infectious diseases, yet their dynamics and impact on HIV/SIV infection have not yet been assessed. We hypothesized that SIV infection and the related microbial translocation trigger NET activation and release (NETosis), and we investigated the interactions between NETs and immune cell populations and platelets. We compared and contrasted the levels of NETs between SIV-uninfected, SIV-infected, and SIV-infected antiretroviral-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 24 publications
2
69
0
Order By: Relevance
“…Historically, it has been shown that both uninfected RMs [73] and HIV-uninfected patients [53,112] tend to have very small numbers of neutrophils resident in the gut, so their presence in AGMs suggests some role in responding to SIV infection. One possible explanation is that the resident gut neutrophils respond immediately to any possible leakage, no matter how minimal, from the gut lumen during the acute infection, through mechanisms like phagocytosis and the release of NETs [113,114]. Indeed, we did see a significant increase in the number of MPO-positive cells in the colon only during the ramp-up period, possibly indicating a transient increase of neutrophils during the earliest period following infection.…”
Section: Plos Pathogensmentioning
confidence: 76%
“…Historically, it has been shown that both uninfected RMs [73] and HIV-uninfected patients [53,112] tend to have very small numbers of neutrophils resident in the gut, so their presence in AGMs suggests some role in responding to SIV infection. One possible explanation is that the resident gut neutrophils respond immediately to any possible leakage, no matter how minimal, from the gut lumen during the acute infection, through mechanisms like phagocytosis and the release of NETs [113,114]. Indeed, we did see a significant increase in the number of MPO-positive cells in the colon only during the ramp-up period, possibly indicating a transient increase of neutrophils during the earliest period following infection.…”
Section: Plos Pathogensmentioning
confidence: 76%
“…NETs are highly detected in the tracheal aspirate and lung tissue from COVID-19 patients Lung inflammation is the primary cause of life-threatening respiratory disorder in critical and severe forms of COVID-19 (Guan et al, 2020). NETs have been identified in the lung tissue of viral and nonviral infected patients and experimental animals (Sivanandham et al, 2018;Dicker et al, 2018). We next investigated the content of NETs in the tracheal aspirate obtained from patients with severe COVID-19 under mechanical ventilation admitted to the intensive care unit or in the lung sections from postmortem COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…In response to myriad external stimuli, neutrophils release potent enzymes such as neutrophil elastase (NE) and myeloperoxidase (MPO) from cytoplasmic granules (Borregaard et al, 2007). Although neutrophils contribute to host immunity, excessive recruitment of neutrophils and their release of granule components along with nuclear chromatin, or neutrophil extracellular traps (NETs), (Brinkmann et al, 2004) aggravate tissue injury and may lead to death in several disease conditions (Xu et al, 2009;Abrams et al, 2013;Sivanandham et al, 2018). NETs lead to a dispersal of toxic molecules: histones and granule proteins such as MPO, NE, and proteinase 3 (Narasaraju et al, 2011;Ashar et al, 2018;Zhu et al, 2018), and, importantly, NETs strongly stimulate the production of pro-inflammatory cytokines (Muller and Radic, 2016).…”
Section: Neutrophilia Is Associated With Fatal Covid-19 Infectionsmentioning
confidence: 99%